Computer modelling of a bacteria dynamics - Katauskis, Pranas; Skakauskas, Vladas (Lietuvos matematikos rinkinys, 2010)
The system of partial differential equations, describing the dynamics of the oxygen consuming bacteria in a chamber with an open top, is investigated. The finite difference method is used for solving the problem. Solutions of two different numerical schemes are compared and analyzed when values of oxygen concentration become negative in the case of a shallow layer.
Keywords: computer simulation; shallow layer; steady-state solution